Control of lipid metabolism by the dynamic and nutrient‐dependent post‐translational modification O‐GlcNAcylation. Issue 2 (9th January 2023) - Schulz, Céline; Lemaire, Quentin; Berthier, Alexandre; Descat, Amandine; Kouach, Mostafa; Vercoutter‐Edouart, Anne‐Sophie; Yazidi‐Belkoura, Ikram El; Hardivillé, Stéphan; Goossens, Jean‐François; Lefebvre, Philippe; Lefebvre, Tony
Abstract: O ‐GlcNAcylation is a post‐translational modification belonging to the large group of glycosylations. It consists of the modification of cytoplasmic, nuclear, and mitochondrial proteins with a single N‐acetylglucosamine residue by O ‐GlcNAc transferase (OGT). Despite its structural simplicity, O ‐GlcNAcylation orchestrates many functions inside the cell. This modification regulates fatty acids synthesis, fat storage, and utilization. The generation of white and brown adipocyte‐OGT knock‐out mice has highlighted the marked interference of O ‐GlcNAcylation in adiposity and, as a consequence, in metabolic pathologies. OGT is more especially involved in the regulation of lipolysis, and thermogenesis in brown adipose tissue. In addition, O ‐GlcNAcylation directly regulates fatty acid synthase, the main enzyme responsible for fatty acids synthesis, and other lipogenic enzymes and transcription factors. Nevertheless, only a few studies reported connections between O ‐GlcNAcylation and homeostasis of cholesterol or its derivatives. This knowledge gap is surprising due to the crucial importance of cholesterol in structuring animal biological membranes and as a precursor of a wide variety of biological compounds. Here, we review the current literature about this topic and discuss future prospects in the field. Key points: As a PTM, O ‐GlcNAcylation exponentially expands protein functions. O ‐GlcNAcylation orchestrates many biological functions in living beings including metabolic fluxes. O ‐GlcNAcylation is crucial for fat storage and mobilization, and for fatty acid synthesis but its function in the metabolism of other lipid compounds is less documented. Abstract :